Coupling interactions and spatial equilibrium analysis of water-energy-food in the Yellow River Basin, China. (January 2023) - Wang, Yirui; Song, Jinxi; Sun, Haotian
Highlights: The coupling of WEF reached benign coordination with a U-shaped spatial pattern. A spatial equilibrium degree model is used to quantify the spatial equilibrium of WEF. The multi-scale spatial equilibrium pattern of WEF is evaluated. A new view for dividing the boundary of spatial equilibrium is provided. Returning farmland to forest has impact on spatial equilibrium of some indicators. Abstract: With respect to the ecological protection and high-quality development of the Yellow River Basin (YRB), research on water-energy-food (WEF) is important for regional sustainable development. This study established an indicator system for the WEF system, and used the coupling coordination degree and decoupling model to analyze the coupling relationship of the WEF system. The multi-scale spatial equilibrium pattern was also evaluated using spatial equilibrium methods. And the results indicated that: 1) the development level of WEF in YRB increased during 2000-2019, and the coupling coordination degree developed from imminent unbalance to moderate coordination phase with a U-shaped spatial pattern; 2) the area with the optimum state of the decoupling relationship gradually expanded, and overall regional coordination significantly improved; 3) the spatial equilibrium degree increased from northwest to southeast, with the Hu Line being the dividing line and the Bole-Taipei Line being the boundary of spatial equilibrium. This study provides a scientific basis for strengthening the management of YRB, and achieving regional sustainable development.